Ose mravljarice Slovenije (Hymenoptera: Mutillidae) - Gogala, Andrej (Scopolia, 2017)
Velvet ants (Mutillidae) are a cosmopolitan family of aculeate wasps, characterized by extreme sexual dimorphism. Larvae are external parasitoids of larvae or pupae of other insects in their nests or hiding places. The list of velvet ants of Slovenia is based on data from the literature, the late Guido Nonveiller's handwritten list of species in the collection of Evgen Jaeger and specimens from the collection of the Slovenian Museum of Natural History in Ljubljana (PMSL). Sixteen species of velvet ants have been recorded for Slovenia. Data for the following four species are published for the first time: Physetopoda cingulata, Physetopoda daghestanica, Smicromyrme sicanus and Cystomutilla ruficeps. Additional 6 species represented in the PMSL collection only by specimens from other countries (mostly from the Balkans) are listed separately.
Keywords: Cystomutilla ruficeps; entomological species; Hymenoptera; kožokrilci; Mutillidae; ose; ose mravljarice; Physetopoda cingulata; Physetopoda daghestanica; Prirodoslovni muzej Slovenije; Slovenia; Slovenian Museum of Natural History; Slovenija; Smicromyrme sicanus; velvet ants; zoological collections; zoologija; zoology; zoološke zbirke; žuželke